Meningkatkan Self Efficacy Matematika Siswa Sekolah Menengah Pertama Melalui Model Pembelajaran Kooperatif Tipe NHT - Misnasanti, Misnasanti; Jailani, Jailani (FKIP Universitas Mataram, 2020)
AbstractThe low mathematics self efficacy of junior high school students and the infrequency of teachers using learning models that can enhance students 'self efficacy in learning mathematics encourage researcher to conduct classroom action research aimed to increase students' mathematics self efficacy and to improve the quality of mathematics learning through NHT type of cooperative learning model. The population was all students of grade VII SMP 12 Yogyakarta and sample was students of class VII-D. Data collected by questionnaire, observation, field notes and tests. This research was said to be successful if the students' self-efficacy increase with moderate criteria reached 33.33% and the high criteria reached 53%. Learning was said to be successful if there were at least 75% of students who complete with a passing grade minimal 75. Learning worked well when the learning process reached 90%. The results showed that learning using the NHT learning model can improve students' mathematics self efficacy. The average score of students' mathematics self efficacy questionnaire obtained from student questionnaire data has increased in each cycle. The implementation of learning has increased from cycle I which showed an average of 74% to cycle II with an average of 93%. Cognitive test results obtained indicate an increase in cognitive test results from cycle I to cycle II.ÃÂ AbstrakMasih rendahnya self efficacyÃÂ matematika siswa SMP dan masih jarangnya guru menggunakan model pembelajaran yang dapat menumbuhkan dan meningkatkan self efficacy siswa dalam belajar matematika mendorong peneliti untuk melakukan penelitian tindakan kelas yang bertujuan untuk meningkatkan self efficacy matematika siswa dan meningkatkan kualitas pembelajaran matematika melaluiÃÂ model pembelajaran kooperatif tipe NHT. Populasi dalam penelitian ini adalah semua siswa kelas VII SMP Negeri 12 Yogyakarta dengan sampel penelitian adalah siswa kelas VII-D. Data dikumpulkan dengan angket, observasi, catatan lapangan dan tes. Penelitian ini dikatakan berhasil jika self efficacy siswa meningkat dengan kriteria sedang mencapai 33,33% dan kriteria tiggi mencapai 53%. Pembelajaran dikatakan berhasil jika minimal terdapat 75% siswa yang tuntas dengan nilai ketuntasan Ã¢â°Â¥75. Pembelajaran berhasil terlaksana dengan baik apabila proses pembelajaran mencapai 90%. Hasil penelitian menunukkan bahwa pembelajaran menggunakan model pembelajaran NHT dapat meningkatkan self efficacy matematika siswa. Rata-rata skor angket self efficacy matematika siswa yang diperoleh dari data angket siswa mengalami peningkatan pada setiap siklus. Keterlaksanaan pembelajaranÃÂ mengalami peningkatan dari siklus I yang menunjukkan rata-rata 74% ke siklus II dengan rata-rata 93%. Hasil tes kognitif yang diperoleh menunjukkan adanya peningkatan hasil tes kognitif dari siklus I ke siklus II.